Degrasyn-like Symmetrical Compounds: Possible Therapeutic Agents for Multiple Myeloma (MM-I) - Peng, Zhenghong (2014)
A series of degrasyn-like symmetrical compounds have been designed, synthesized, and screened against B cell malignancy (multiple myeloma, mantle cell lymphoma) cell lines. The lead compounds T5165804 and CP2005 showed higher nanomolar potency against these tumor cells in comparison to degrasyn and inhibited Usp9x activity in vitro and in intact cells. These observations suggest that this new class of compounds holds promise as cancer therapeutic agents